Valuing water in irrigated agriculture and reservoir fisheries: a multiple-use irrigation system in Sri Lanka - Renwick, M.E. (International Water Management Institute, 2001)
Although irrigation projects often provide water for more than crop irrigation, water allocation and management decisions often do not account for nonirrigation uses of water. Failure to account for the multiple uses of irrigation water may result in inefficient and inequitable water allocation decisions. Decision-makers often lack information on the relative economic contributions of water in irrigation and nonirrigation uses. This report addresses this problem. It examines the relative economic contributions of irrigated agriculture and reservoir fisheries in the Kirindi Oya irrigation system, located in southeastern Sri Lanka. The results of the analysis indicate the importance of both irrigated paddy production and reservoir fisheries to the local economy. They also demonstrate significant potential financial and economic gains to irrigated agriculture from improvements in water management practices.